Girl, wash your face stop believing the lies about who you are so you can become who you were meant to be - Hollis, Rachel (Nelson Books, an imprint of Thomas Nelson, 2018)
Founder of the lifestyle website TheChicSite.com and CEO of her own media company, Rachel Hollis has created an online fan base by sharing tips for living a better life while fearlessly revealing the messiness of her own. Each chapter begins with a specific lie Hollis once believed that left her feeling overwhelmed, unworthy, or ready to give up. As a working mother, a former foster parent, and a woman who has dealt with insecurities about her body and relationships, she speaks with the insight and kindness of a BFF, helping women unpack the limiting mind-sets that destroy their self-confidence and keep them from moving forward. From her temporary obsession with marrying Matt Damon to a daydream involving hypnotic iguanas to her son's request that she buy a necklace to "be like the other moms," Hollis holds nothing back. With unflinching faith and tenacity, Hollis spurs other women to live with passion and hustle and to awaken their slumbering goals.